Yoruba Women and Politics: A Postcolonial Feminist Perspective from Ijebu Women, Southwest Nigeria - AKANNI, Bolaji Olaronke (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
The political participation of Ijebu women in Nigeria presents an essential opportunity for exploration, as it is shaped by various systemic challenges rooted in historical, cultural, and socio-economic factors. While much has been written about the progress of gender equality globally and women's political participation in Nigeria, particularly among the Yoruba, this paper aims to enhance our understanding by focusing on the Ijebu women. Exploring their unique experiences and contributions highlights how these women navigate and influence the political landscape. This paper recognises the tremendous achievements of Ijebu women in politics, while also addressing the problems they encounter and detailing the reforms required to foster wider inclusion. It examines the impact of traditional norms, patriarchal structures, and modernisation on women's access to political power and decision-making positions. By utilising a postcolonial feminist framework, this study emphasises the importance of understanding the intersections of gender, colonial legacies, and socio-political structures in shaping women's participation in governance. Through this lens, actionable steps to empower Ijebu women and enhance their role in political leadership are identified. The paper offers actionable insights for developing more inclusive and representative governance structures in the region. It concludes with constructive recommendations aimed at increasing Ijebu women's political engagement through initiatives in education, policy reforms, economic empowerment, and enhanced media representation.